2013
DOI: 10.1039/c3cc47264g
|View full text |Cite
|
Sign up to set email alerts
|

An improved fluorogenic NAD(P)+ detection method using 2-acetylbenzofuran: its origin and application

Abstract: We have developed a fluorogenic NAD(P)(+) detection method using 2-acetylbenzofuran. The reaction of NAD(P)(+) with 2-acetylbenzofuran produced a fluorescent product, allowing the highly-sensitive and quick detection of NAD(P)(+). This method was successfully applied to the detection of P450 substrates in the microtiter-plate format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…24 The fact that the presented methodology can also be used to measure NADPH consumption shows that the setup is not limited to fluorogenic and chromogenic substrates. However, although NADPH oxidation has been applied as a generic method for measuring CYP activities, [25][26][27] it does not necessarily represent product formation because several substrate/CYP combinations show a high degree of uncoupling, as is the case with metabolism of alkoxyresorufins by CYP BM3 mutants. The most generic method therefore would be online detection of metabolites by MS, as has been successfully applied for analysis of products formed by CYP BM3mediated metabolism of steroids and p38α kinase inhibitors.…”
Section: Cyp Bm3-mediated Metabolism Of the Drug Amitriptylinementioning
confidence: 99%
“…24 The fact that the presented methodology can also be used to measure NADPH consumption shows that the setup is not limited to fluorogenic and chromogenic substrates. However, although NADPH oxidation has been applied as a generic method for measuring CYP activities, [25][26][27] it does not necessarily represent product formation because several substrate/CYP combinations show a high degree of uncoupling, as is the case with metabolism of alkoxyresorufins by CYP BM3 mutants. The most generic method therefore would be online detection of metabolites by MS, as has been successfully applied for analysis of products formed by CYP BM3mediated metabolism of steroids and p38α kinase inhibitors.…”
Section: Cyp Bm3-mediated Metabolism Of the Drug Amitriptylinementioning
confidence: 99%
“…31 By analogy with chelerythrine with its quaternary ammonium group that is linked by three carbons to an oxygen, we aimed to develop 8-hydroxy-2,7-naphthyridin-2-ium salts (3) as potential inhibitors of AChE and BChE. The synthesis of the highly fluorescent 8-hydroxy-2,7-naphthyridin-2ium salts, as well as their conjugated bases, the 2,7naphthyridin-1IJ7H)-ones, has already been published, [32][33][34][35] however, no distinct biological activity has been attributed to this chemotype. Instead, the formation of 8-hydroxy-2,7naphthyridin-2-ium salts was utilized as an operating principle of several fluorescence-based assay methods to detect nicotinamide and its analogues.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, therefore, we sought sensitive NAD(P) + detection reagents and platforms 34 to be used as high-throughput P450 substrate screens, and found that 2-acetylbenzofuran (2-ABF), which generates fluorescent 2,7-naphthyridinone derivatives upon reaction with NAD(P) + , is a more sensitive, efficient, and inexpensive NAD(P) + detection reagent compared with the pre-existing reagent (Fig. 1a) 35 . 2-ABF reacts with NAD + 20 times faster than acetophenone, the standard reagent, and detects NAD + with 1000-fold greater sensitivity 35 .…”
Section: Resultsmentioning
confidence: 99%
“…1a) 35 . 2-ABF reacts with NAD + 20 times faster than acetophenone, the standard reagent, and detects NAD + with 1000-fold greater sensitivity 35 . The NAD(P) + detection method using 2-ABF, termed the 2-ABF method, is thought to be well-suited for microtiter plate-based screening of P450 substrates.
Figure 1Summary of the integrated P450 substrate screening system.
…”
Section: Resultsmentioning
confidence: 99%